Video Animasi 3D Cluster The Rich Sebagai Media Promosi Pada Ciptaland Development - Reynaldi Reynaldi; Ibrahim Ibrahim (INCODING: Journal of Informatics and Computer Science Engineering, 2022)
Various media as a place to get information are now easy to get, currently Ciptaland Development itself uses several more common marketing methods, for example, marketing via online but limited to collaborating with third parties, utilizing local media for example print media or brochures, flexible service to customers. Consumers, product exhibitions at malls or other events and provide product quality assurance to consumers. These methods or media are commonly used to disseminate information. According to most people, they are not satisfied with the information about the product that has been delivered in the ways that have been done. The purpose of this research is to make Cluster The Rich Promotional Video, which is a marketing and sales tool with different media than before. The method used is to collect information about Cluster The Rich from the parties concerned and to directly observe the location where the Cluster The Rich will be built. The conclusion is that this Promotional Video was successfully created using SketchUp Software, followed by rendering with V-Ray Software and then edited using Adobe Premiere Pro. The advantage of this Promotional Video is that it conveys direct visuals about 3D-shaped objects so that they are more attractive than previous promotions that are only in the form of images.